2022
DOI: 10.4018/ijehmc.309429
|View full text |Cite
|
Sign up to set email alerts
|

Combating Drug Counterfeiting by Tracing Ownership Transfer Using Blockchain Technology

Abstract: Supply chain management in healthcare sector plays significant role in the lives of people. Presence of intermediaries and lack of traceability has lured it towards drug counterfeiting, which reduces drug efficacy, thus hampering patients' trust and putting their lives in danger. Blockchain has emerged as a groundbreaking technology which provide a system that is immutable and transparent without the requirement of a trusted third party. This paper depicts how blockchain can provide a solution to reduce drug c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It is a set of timestamped, immutable blocks connected by cryptographic hashes. Each new block that has been inserted at the end of the chain contains a special code or a reference to the data that was added to a previous block [5]. Blockchain technology is mostly used to improve product safety and ensure accurate pharmaceutical product traceability.…”
Section: Introductionmentioning
confidence: 99%
“…It is a set of timestamped, immutable blocks connected by cryptographic hashes. Each new block that has been inserted at the end of the chain contains a special code or a reference to the data that was added to a previous block [5]. Blockchain technology is mostly used to improve product safety and ensure accurate pharmaceutical product traceability.…”
Section: Introductionmentioning
confidence: 99%
“…The ledger is stored in a block that is almost impossible to mold and can be updated only through a consensus protocol agreed by all connected nodes in the blockchain network. Bali et al (2021) have suggested a solution for combating drug counterfeiting by tracing the ownership transfer using blockchain technology. The first practical solution provided by blockchain technology is the cryptocurrency Bitcoin.…”
Section: Introductionmentioning
confidence: 99%